Bacterial contamination of single and multiple-dose parenteral injection vials after opening and antibiotic susceptibility of isolates at Jimma Medical Center, Jimma, Southwest Ethiopia - Abay Tabor; Zewudineh Shalemariam; Yared Alemu; Kasahun Gorems (Elsevier, 2023)
Summary: Background: Single- or multiple-dose vials are prone to bacterial contamination after improper handling and can be potential reservoirs of microorganisms that could be transmitted to the patient through the parenteral route. The present study aims to assess the magnitude of the problem and associated factors at Jimma Medical Center (JMC), Jimma, Southwest Ethiopia. Methods: A cross-sectional study design was conducted at JMC from July 2021 to October 2021. A total of 384 parental medications and nurse interviews that were administered in 11 wards and 3 intensive care units were included. Samples were processed and identified by conventional bacterial culture methods. Results: The overall prevalence of vial contamination due to aerobic bacteria was 21 (5.5%) among multiple-dose vials and none of the single-dose vials. The highest level of contamination (8, 38.1%) was found in the paediatric ward. Pseudomonas aeruginosa and Klebsiella pneumoniae were the most common microorganisms identified vial contamination, 6 cases (28.5%) and 5 cases (23.8%) respectively Multidrug resistance was identified in 95.2% of the isolates, with all Gram-negative isolates showing a multidrug resistance against the tested antibiotics. In multivariate logistic regression analysis, vial contamination was strongly associated with reuse of syringe and/or needle, the environment where medication was handled, and the storage conditions. Conclusion: In this study, the prevalence of vial contamination was high. The bacterial isolates from vials were also resistant to commonly prescribed antimicrobial drugs. Healthcare professionals must strictly adhere to basic infection control practices as per standard guidelines to reduce the risk of infection from contaminated vials.